The HUBUNGAN ANTARA PERILAKU KERJA DENGAN KEJADIAN KECELAKAAN KERJA PADA TENAGA KESEHATAN DI RUMAH SAKIT HJ BUNDA HALIMAH BATAM - 2115098, Irma Fajriah (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
The goal of occupational health and safety (K3) is to minimize risks to both employees and other people who may be in the workplace. The level of knowledge and education, as well as the level of attention, are internal elements that influence behavior at work. While external variables include the impact of infrastructure, facilities, and natural disasters. The purpose of this study was to determine whether there is a relationship between work behavior and the incidence of work accidents among medical personnel at Hj Bunda Halimah Hospital Batam. This study used a cross-sectional research. Random sampling was used to choose the study sample. Based on the findings of the employee questionnaire responses, samples that satisfy the inclusion criteria and do not satisfy the exclusion criteria will be analyzed by recording the research variables. The result showed that 35 individuals (70%) demonstrated a high level of knowledge, followed by 42 people (84%), 36 people (72%) with a background of D3+ education, and 34 people (68%) with solid work ethics. The effects of knowledge level, education level, and usage of PPE on the work behavior of healthcare personnel at Hj Bunda Halimah Hospital Batam, with p values of 0.001, 0.044, and 0.000, respectively. In conclusion, there is a correlation between the knowledge, education, and use of PPE for health workers and their behavior at work At the Hj Bunda Hamilah Hospital in Batam.